Acute leukemias with ETV6/ABL1 (TEL/ABL) fusion: poor prognosis and prenatal origin - Zuna, Jan; Zaliova, Marketa; Muzikova, Katerina; Meyer, Claus; Lizcova, Libuse; Zemanova, Zuzana; Brezinova, Jana; Votava, Felix; Marschalek, Rolf; Stary, Jan; Trka, Jan (Genes, chromosomes & cancer, 2010)
The ETV6/ABL1 (TEL/ABL) fusion gene is a rare aberration in malignant disorders. Only 19 cases of ETV6/ABL1-positive hematological malignancy have been published, diagnosed with chronic myeloid leukemia, other types of chronic myeloproliferative neoplasm, acute myeloid leukemia or acute lymphoblastic leukemia (ALL). This study reports three new cases (aged 8 months, 5 years, and 33 years) of ALL with the ETV6/ABL1 fusion found by screening 392 newly diagnosed ALL patients (335 children and 57 adults). A thorough review of the literature and an analysis of all published data, including the three new cases, suggest poor prognosis of ETV6/ABL1-positive acute leukemias. The course of the disease in the two pediatric patients is characterized by minimal residual disease monitoring, using quantification of both the ETV6/ABL1 transcript and immunoreceptor gene rearrangements. Eosinophilia could not be confirmed as a hallmark of the ETV6/ABL1-positive disease. Studies of neonatal blood spots demonstrated that, in the child diagnosed at five years, the ETV6/ABL1 fusion initiating the ALL originated prenatally.
Keywords: novorozenec; Infant, Newborn; Neoplasm, Residual; Humans; messenger RNA; dítě; Oligonucleotide Array Sequence Analysis; In Situ Hybridization, Fluorescence; Child; fúzní onkogenní proteiny; Female; Neonatal Screening; dospělí; polymerázová řetězová reakce s reverzní transkripcí; lidé; tyrosinkinasy; srovnávací genomová hybridizace; novorozenecký screening; Reverse Transcriptase Polymerase Chain Reaction; Oncogene Proteins, Fusion; předškolní dítě; Adult; RNA, Messenger; ženské pohlaví; Male; Protein-Tyrosine Kinases; hybridizace in situ fluorescenční; prognóza; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Gene Rearrangement; akutní lymfatická leukemie; genová přestavba; mužské pohlaví; prospektivní studie; Child, Preschool; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Comparative Genomic Hybridization; Prognosis; reziduální nádor; Prospective Studies